2016
DOI: 10.1111/jocn.13670
|View full text |Cite
|
Sign up to set email alerts
|

The mental healthcare needs of undocumented migrants: an exploratory analysis of psychological distress and living conditions among undocumented migrants in Norway

Abstract: We recognised a need for an interdisciplinary and dynamic approach to mental health care. Undocumented migrants are in need of a minimum of psychological and material support assuring basic needs such as shelter and appropriate food and access to health care and social welfare.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
50
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 31 publications
(87 reference statements)
4
50
0
2
Order By: Relevance
“…This, according to Ager and Strand (2008), is a vital resource to facilitate the integration of refugees to overcome their problems while settling in new communities. This finding is inconsistent with previous studies which reported that refugees are usually not accepted in their new communities (Basheti et al, 2015;Myhrvold & Småstuen, 2017;Shick et al, 2016;Reinelt et al, 2016). For example, Holmes et al, (2017) Joyce and Liamputtong (2017), stated that the western culture of individualism and independence makes it hard for refugees who find themselves in such environment to resettle and integrate with members of the community effectively.…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…This, according to Ager and Strand (2008), is a vital resource to facilitate the integration of refugees to overcome their problems while settling in new communities. This finding is inconsistent with previous studies which reported that refugees are usually not accepted in their new communities (Basheti et al, 2015;Myhrvold & Småstuen, 2017;Shick et al, 2016;Reinelt et al, 2016). For example, Holmes et al, (2017) Joyce and Liamputtong (2017), stated that the western culture of individualism and independence makes it hard for refugees who find themselves in such environment to resettle and integrate with members of the community effectively.…”
Section: Discussionmentioning
confidence: 62%
“…Similarly, Akua-Sakyiwah (2017) found that differences in language make it hard for refugees to partake in income generation activities and thus, compound their vulnerability. There are also instances where refugees had to flee immigration and security officers for fear deportation (Myhrvold & Småstuen 2017). Although this did not emerge in this study, there are reports of brutalities melted on refugees by the Cameroonian army (Human Rights Watch, 2017).…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The literature shows contradictory results in relation to the effect of educational level of people who emigrate. Having a university degree was a predictor of worse general health among refugee adults in Australia (22) while it was a protective factor in refugees, where having higher education predicted fewer medical conditions (23) and less psychological distress (24). The pre-migration conditions that in some studies had appeared as a strong predictor of depression and other psychological disorders were not supported in this hypothesis (25).…”
Section: Discussionmentioning
confidence: 92%
“…Vi vet at papirløse migranter i Norge lever ustabile liv preget av fattigdom og mangel på fast bolig (5,6), og at de har liten tilgang til helsetjenester. Fordi mange av pasientene kommer fra land med høy forekomst av infeksjonssykdommer, hadde vi forventet å finne flere tilfeller av smitteførende infeksjonssykdommer, selv om under halvparten av pasientene ble testet.…”
Section: Diskusjonunclassified